(untitled) (Research, Society and Development, 2022)
Objective: To realize an epidemiological analysis of the population diagnosed with HIV/AIDS in the 7th Health Regional Office in the state of Paraná (7th RS-PR), Brazil, between the years 2009 and 2019. Methodology: Observational epidemiological study of the descriptive-retrospective type, with a quantitative approach, conducted from secondary data of AIDS cases notification from the Department of Chronic Conditions Diseases and Sexually Transmitted Infections made available by the Ministry of Health between 2009 and 2019. A descriptive statistical analysis was performed using the Kruskal-Wallis test. Results: The Kruskal-Wallis statistical test showed by means of the Chi-Square (X2) that for all variables evaluated the p-values observed were <0.005, indicating that the categories of individuals differ at 5% probability among the categories of individuals with HIV evaluated. 360 new cases of HIV/AIDS were reported in the 7th SR-PR, with the highest incidence (11.3%) in 2017. 53.3% are male and, 71.0% are declared white. Sexual transmission accounts for 96.4% of cases, with transmission among heterosexuals being more prevalent. According to education, those with incomplete elementary school (19.7%) were more affected by the disease. Conclusion: Geographic patterns, cultural and social habits, and access to information about HIV infection reflect in the population profile most affected by the disease. The highest prevalence rates of HIV/AIDS cases were in white, heterosexual men with incomplete elementary school education.